Terengganu traditional house interior space and illumination planning for Terengganu tradisional dwelling - Awawdeh, Tawfeeq Naser
Interior design is the overall design of the internal spaces, the purpose of which is to harness the physical, spiritual, and social needs of the people and, in turn, guarantee the safety of the building. Recent studies have pointed to the importance of interior design, including space planning and the level of lighting in houses and their impact on the quality of individuals living in the house. Therefore, it is necessary to focus on the quality of the space planning of the house in accordance with the needs and requirements of individuals. Through the presence of the researcher in Kuala Terengganu, Besut, and Setiu, the researcher observed the nature and quality of traditional dwellings and noted that the traditional houses lack some characteristics, such as the quality of the space planning, which significantly affect the level of privacy of individuals living in the house and suitable lighting level which significantly affect the level of comfort of individuals. Therefore, this study aims at determining the effect of space planning and lighting on traditional houses in traditional houses Terengganu. This study applied quantitative methods. The quantitative approach was used to collect the data from the study sample; a questionnaire was designed as the primary tool for collecting data. It included 50 items divided into two variables: space planning consisting of 25 items, and lighting consisting of 25 items. The sample was comprised of 325 citizens of Terengganu that was simple random sampling. The respondents' age was above 28 years, all being Terengganu citizens to get the appropriate feedback regarding this study. After the distribution of the questionnaire and data collection, Statistical Package for Social Sciences (SPSS) was used to analyse the study questions through the use of factor analysis and cluster analysis. The study found that there is 72 percent of the respondents required the touch of interior designer in the space planning of the Terengganu traditional house, 83 percent confirmed that the colour element was the most important element that has an impact on visual perception. As for lighting, the proportion of respondents was 89 percent who confirmed that the lighting colour is crucial to reach the visual comfort, 90 percent of the respondents confirmed that the dispersion of natural lighting in the Terengganu traditional house was good enough. In conclusion, the space planning element is important in the planning of the interior space of houses. Also, the lighting element is an essential element inside the house, as lighting is a source for residents' comfort. Therefore, in this study we recommended elements should be considered by interior designers as crucial elements.